1991
DOI: 10.1007/bf00587828
|View full text |Cite
|
Sign up to set email alerts
|

Serial MR imaging in Creutzfeldt-Jakob disease

Abstract: Serial magnetic resonance (MR) imagings of two autopsied patients with Creutzfeldt-Jakob disease (CJD) are presented. Both patients showed a dramatic progression of brain atrophy. The initial MR imagings were, however, interpreted as normal except for localized mild cortical atrophy in one patient. When a normal MR image is obtained in a demented middle-aged or aged patient, CJD may still need to be ruled out: follow up MR imaging may be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…All these disorders demonstrate prolonged T2 relaxation, except for Hallervorden Spatz disease, which often shows pronounced hypointensity on the long TR images in the basal ganglia from iron deposit. Symmetry of the findings makes neoplastic lesions very unlikely [6,7]. Although there is a wide range of differential diagnoses, we believe that, considering clinical course and EEC examination, characteristic signal alterations on early MRI are definitely helpful for evaluating the clinical diagnosis of early-stage CJD in patients with rapidly progressive dementia.…”
Section: Discussionmentioning
confidence: 95%
“…All these disorders demonstrate prolonged T2 relaxation, except for Hallervorden Spatz disease, which often shows pronounced hypointensity on the long TR images in the basal ganglia from iron deposit. Symmetry of the findings makes neoplastic lesions very unlikely [6,7]. Although there is a wide range of differential diagnoses, we believe that, considering clinical course and EEC examination, characteristic signal alterations on early MRI are definitely helpful for evaluating the clinical diagnosis of early-stage CJD in patients with rapidly progressive dementia.…”
Section: Discussionmentioning
confidence: 95%
“…The nature of the white matter abnormalities remains obscure, but can possibly be attributed to Wallerian degeneration. 6 Most CT or MRI abnormalities in human prion diseases in previous reports mention either no abnormalities, cortical atrophy, or high signal intensities in the basal ganglia. White matter abnormalities, as we report, appear to be rare in spongiform encephalopathy, which is referred to as the panencephalopathic type of Creutzfeldt-Jakob disease (CJD).…”
Section: Discussionmentioning
confidence: 98%
“…White matter abnormalities, as we report, appear to be rare in spongiform encephalopathy, which is referred to as the panencephalopathic type of Creutzfeldt-Jakob disease (CJD). 6 There are only a few case reports of sporadic CJD with white matter degeneration and cortical atrophy. 6,7 Including our patient, at least four patients with a hereditary prion disease have had white matter changes.…”
Section: Discussionmentioning
confidence: 98%
“…3) (8). With the evolving course of the disease, atrophy is seen, a finding usually revealed after the typical DWI changes (8,41). A large multinational study demonstrated that abnormal signal in the basal ganglia was found in 71% on DWI, and 63% on FLAIR, whereas widespread abnormal signal within the cortex was found in 66% on DWI and 38% on FLAIR (6).…”
Section: Sporadic Creutzfeldt-jakob Diseasementioning
confidence: 99%